Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/17565529.2018.1442805
|View full text |Cite
|
Sign up to set email alerts
|

On-farm cocoa yields increase with canopy cover of shade trees in two agro-ecological zones in Ghana

Abstract: Despite Ghana's large contribution to global cocoa production, average yields are low. Policymakers and practitioners are calling for implementation of a climate smart strategy by increasing yields and augmenting shade tree cover in cocoa systems. However, there have been few studies in West Africa on the relationship between shade and cocoa yield under field conditions. The objective of this study was to determine the effect of shade tree cover and other factors on on-farm cocoa yields over a four-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Higher yields in UEMZ and MEZ can be attributed to more favourable rainfall conditions (Vigneri, 2007) compared to DSFZ. Yields from the MEZ in the Western region were higher than in DSFZ in the Ashanti region and this is consistent with Asare et al (2018) and Madsen & Helledie (2018).…”
Section: Organic Carbon Stored and Pod Count Relationshipsupporting
confidence: 89%
“…Higher yields in UEMZ and MEZ can be attributed to more favourable rainfall conditions (Vigneri, 2007) compared to DSFZ. Yields from the MEZ in the Western region were higher than in DSFZ in the Ashanti region and this is consistent with Asare et al (2018) and Madsen & Helledie (2018).…”
Section: Organic Carbon Stored and Pod Count Relationshipsupporting
confidence: 89%
“…The most important strategy for decreasing HANPP in cocoa dominated landscapes is to encourage the cultivation of shade trees. Research has also shown that cocoa yields can increase with increasing canopy cover provided by shade trees (Schroth et al, 2017;Asare et al, 2019), further strengthening the case that the key to climate smart strategies for cocoa is the presence of shade trees. Increasing shade tree cover not only reduces HANPP, but has other benefits including increased biodiversity and possibly more resilience of the cocoa crop to climate extremes and regional warming (Rice and Greenberg, 2000;Schroth et al, 2016).…”
Section: Npp and Hanpp Of Complex Mosaic Landscapementioning
confidence: 89%
“…However, yields have also been reported to decline faster in these conditions (Obiri et al 2007), particularly where no fertiliser is used (Ahenkorah et al 1974). Canopy cover up to 39% has been shown in increase bean yields at the field level in Ghana compared to cacao grown in full sun, but increasing shade above this level can limit yields Asare et al 2018). While in Cameroon, increasing canopy cover up to 47% enhanced yield but greater than 60% cover caused yield limitations (Bisseleua et al 2009).…”
Section: Irradiancementioning
confidence: 99%